Lutando por corações, mentes e credencias: as disputas em torno da regulamentação da profissão de jornalista no Brasil na primeira década do século XXI - Nascimento, Lerisson Christiam (2014)
The aim of this paper is to show how journalism in Brazil - between the end of the 20th century and the beginning of the 21st century was the subject of disputes in the academic field and in the scope of professional regulation. We show how these two processes relate through the relationship between the idea of professionalism and the process of building a specific knowledge about journalism in the national academic field.